ADMINISTRATIVE LEGAL PROCEDURES IN THE SPHERE OF PUBLIC ADMINISTRATION OF UKRAINE - Borodin, Ivan L.; Myronets, Oksana M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the task of scientific research is to determine a concept of administrative legal procedures, also, basic directions to solve problems of their legal support in Ukraine. The administrative procedures according to the nature of their legal influence on social relations have been classified and analyzed. Methods: general scientific, philosophical and specially-legal methods of the scientific research have been used. A system analysis method has been used to determine rulemaking, adoption of individual acts of public administration, control procedures. A dogmatic method was valuable to formulate conclusions and recommendations of practical character within the research issues concerning the determination of investigated administrative legal procedures at the legislative level of Ukraine. Results: particularities of three groups of administrative procedures id est: a) rulemaking; b) adoption of individual acts of public administration; c) control have been defined, the stages and problems of their implementations have been investigated. Discussion: national legislation concerning the administrative legal procedures. The lack of regulations that would determine a procedure for rights and duties implementation, provided by substantive norms in the field of public administration, leads to the fact that those substantive rules do not work. The development of administrative legal procedures and the investigation of problems of their implementation is an important topic for the future research.